Model Komunikasi Bisnis Jual Beli Buku Melalui Komunikasi Interpersonal dan Komunitas Grup Facebook - Pranawukir, Iswahyu; Hamboer, Maria Jashinta Elisabet (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
An online transaction activities are involving exchange of messages and information. This is actually part human activities in order to fulfill the human’s need which is also part of what socalled business communication. Business communication itself has been improved and developed in many fields in recent years. Selling books online and using the social media platform such as Facebook is one of them. This study aims to study the business communication model of selling books using particularly the social media platform of Facebook as a medium. In this context, the sellers play a role as the communicators while the buyers in the position of communicants.Through both method of non-participatory and participatory observations, this study shows there are three categories of mainly books that sold online. First is the brand new books (new prints/new text books), second is the used books (known as the secondhand books) and the third is what so called the collectable, rare and antique books. Using an in-depth interview for analysing business communication model and marketing strategies of selling books online in Facebook, it is evidence that both sellers and buyers have been using and optimilising their networks of friendship through their friend list contacts, both for their interpersonal as well as community communications. They utilise the communications among book lovers and book collectors as the most important strategy of their marketing approach. Therefore, it is clear that both personal and social networking are existed side by side in this social media context for the purpose of their business communication. When someone selling a book online in Facebook, they normally would post the image or photo detailing the book which can be seen by all contacts in their networks including those book lovers or book collectors who often would re-sell their book again online, by using the same social media networks. This research also shows that there are only certain kind of books that mostly sought after by people who use online book selling networks in Facebook. This information comes from contents mainly collected from the wall of Facebook. The list of most popular and top selling books are quite long. Any works by the famous Indonesian writer Pramoedya Ananta Toer (PAT) are the most popular ones. People are also looking for books on literature, the leftist, military, history, religion, politics, economics, law, social and cultural issues. Leisure books such as comics and novels are also selling well